1987
DOI: 10.1007/bf02143593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic ethanol treatment on peroxisomal acyl-CoA oxidase activity and lipid peroxidation in rat liver and heart

Abstract: Chronic ethanol administration was shown to increase catalase and acyl-CoA oxidase activities in rat myocardium but did not alter the activity of liver peroxisomal enzymes. As a result of alcohol consumption a 2-3-fold increase in the level of lipid peroxidation was observed in the heart tissue while in the liver the induction was much less pronounced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 16 publications
4
8
0
1
Order By: Relevance
“…In this study, we observed 1.6-fold higher levels of myocardial MDA in ethanol-treated rats than in nonethanol controls, which is consistent with results obtained by others [25]. Ethanolinduced generation of ROS may be mediated by increased myocardial levels of xanthine oxidase [26] and increases in the activity of acyl CoA-oxidase [25]. Ethanolinduced generation of ROS may be mediated by increased myocardial levels of xanthine oxidase [26] and increases in the activity of acyl CoA-oxidase [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we observed 1.6-fold higher levels of myocardial MDA in ethanol-treated rats than in nonethanol controls, which is consistent with results obtained by others [25]. Ethanolinduced generation of ROS may be mediated by increased myocardial levels of xanthine oxidase [26] and increases in the activity of acyl CoA-oxidase [25]. Ethanolinduced generation of ROS may be mediated by increased myocardial levels of xanthine oxidase [26] and increases in the activity of acyl CoA-oxidase [25].…”
Section: Discussionsupporting
confidence: 93%
“…We have confirmed past findings that chronic ethanol consumption induces lipid peroxidation in the myocardium [7][8][9]25], and have added support to prior evidence that exercise training can protect against ethanol-induced oxidative injury in the heart [12]. We have confirmed past findings that chronic ethanol consumption induces lipid peroxidation in the myocardium [7][8][9]25], and have added support to prior evidence that exercise training can protect against ethanol-induced oxidative injury in the heart [12].…”
Section: Discussionsupporting
confidence: 83%
“…Fransen et al, 2012). Alcoholic cardiomyopathy is related to the activation of heart peroxisomal enzymes accompanied by an excessive elevation of non-enzymatic lipid peroxidation (Koepke et al, 2008;Panchenko et al, 1987).…”
Section: Other Systemsmentioning
confidence: 99%
“…Although alcohol consumption resulted in peroxisomal proliferation in humans (17) and alcohol feeding of rats induced cytochrome P450 4A1 (lauryl -hydroxylase (13)) and liver fatty acid binding protein (18), other typical responses to peroxisome proliferators were impaired by ethanol. The excretion of dicarboxylic fatty acids was increased in alcohol-fed animals (13), due to increased lauryl hydroxylase activity but failure of induction of acyl-CoA oxidase (19). Medium chain acyl-CoA dehydrogenase activity, the gene for which has a PPRE in its proximal promoter (20), was reported to be decreased by ethanol feeding (21).…”
mentioning
confidence: 99%